2015
DOI: 10.1007/s12010-015-1571-9
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Melanin by Submerged Culture of Culinary and Medicinal Fungi Auricularia auricula

Abstract: Natural melanin is of great potential value and application in the fields of pharmacology, cosmetics, and functional foods. In the present study, statistically designed experiments were conducted for the optimization of the media to enhance the production of melanin by submerged culture of Auricularia auricula. Glucose, tyrosine, peptone, and CaCO3 were found to have significant effects (P < 0.015) on melanin biosynthesis by a Plackett-Burman experimental design and subsequently optimized using response surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
8
26
0
Order By: Relevance
“…The linear decrease in the absorption with increasing wavelength was observed for Termitomyces melanin similar to that reported by (Zhang et al 2015). Absorption peaks in UV regions occur due to the presence of many conjugated structures in melanin molecule (Ou-Yang et al 2004).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The linear decrease in the absorption with increasing wavelength was observed for Termitomyces melanin similar to that reported by (Zhang et al 2015). Absorption peaks in UV regions occur due to the presence of many conjugated structures in melanin molecule (Ou-Yang et al 2004).…”
Section: Discussionsupporting
confidence: 90%
“…The log of optical density of a melanin solution when plotted against wavelength produces a linear curve with negative slopes. Such characteristic straight lines with negative slopes have been obtained from some melanogenic fungi such as Phyllosticta capitalensis and Auricularia auricula with slope ranging −0.0015 to −0.0030 (Ellis and Griffiths 1974; Suryanarayanan et al 2004; Bin et al 2012; Zhang et al 2015). The slopes of linear plots are often used to identify melanins and matching spectral features in the present work confirms the identity of T. albuminosus melanin.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Several studies have shown that the composition of the growth medium, nature and concentration of carbon and nitrogen sources, minerals, vitamins, temperature, pH, the presence of Melanin 50 oxygen and aeration, light, stress, and irradiation, among others, affect the growth and pigment production in fungi and that the manipulation of the culture conditions can result in enhanced pigment production [41][42][43][44][45][46][47].…”
Section: Factors Influencing the Melanin Productionmentioning
confidence: 99%